Status Externalities in Education and Low Birth Rates in Korea - Kim, Seongeun; Tertilt, Michèle; Yum, Minchul (American Economic Review, 2024)
South Koreans appear to be preoccupied with their offspring's education and also have the lowest total fertility rate in the world. We propose a novel theory with status externalities and endogenous fertility connecting these facts, motivated by novel empirical evidence on private education spillovers. Using a quantitative model calibrated to Korea, we find that fertility would be 28 percent higher without the externality. We explore the effects of government policy: a pro-natal transfer or an education tax can increase fertility and reduce education spending. An education tax of 22 percent together with moderate pro-natal transfers maximizes the current generation's welfare. (JEL D31, D62, E24, I21, I26, I28, J13, O40)